Patch-Clamp Methods and Protocols - Martina, Marzia; Taverna, Stefano; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Since its inception, patch-clamp has continued to be widely considered the gold standard method to record ion channel activity. Patch-Clamp Methods and Protocols, Second Edition, provides a comprehensive collection of new techniques for the development of automated, high-throughput screening systems for pharmacological evaluation, the use of various patch-clamp configurations together with novel molecular biological and imaging methodologies, and enhanced stimulation protocols and perfusion systems. Divided into sections on pharmacology, physiology, and biophysics, the chapters cover methods to generate more physiologically relevant conditions for drug application and screening technologies, recently developed applications such as optogenetic stimulation, advances in whole-cell recordings in freely-moving animals, and novel technologies to create custom microelectrodes designed for reducing the access resistance and improving the rate of molecular diffusion. Patch-clamp is an indispensable technique for conducting pharmacological, physiological and biophysical research aimed at understanding crucial aspects of cellular and network function. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Patch -Clamp Methods and Protocols, Second Edition will provide a useful technical and methodological guide to diverse audiences of electrophysiologists, from students to experienced investigators.
History of Electrophysiology and the Patch-Clamp.- Whole-Cell Patch-Clamp Analysis of Recombinant NMDA Receptor Pharmacology Using Brief Glutamate Applications -- Patch-Clamp Combined with Voltage/Concentration Clamp to Determine the Kinetics and Voltage Dependency of N-methyl-D-aspartate (NMDA) Receptor Open Channel Blockers -- State-of-the-art Automated Patch-Clamp: Heat Activation, Action Potentials, and High Throughput in Ion Channel Screening -- Industrializing Electrophysiology: HT Automated Patch-Clamp on SyncroPatch® 96 Using Instant Frozen Cells -- Planar Patch Clamp for Neuronal Networks–Considerations and Future Perspectives -- Methods for the Study of Synaptic Receptor Functional Properties -- Single-Cell RT-PCR, A Technique to Decipher the Electrical, Anatomical and Genetic Determinants of Neuronal Diversity -- Whole-Cell Voltage-Clamp on Skeletal Muscle Fibers with the Silicone-Clamp Technique -- Multiphoton Imaging Approaches for Studying Striatal Dendritic Excitability -- Investigation of Synaptic Microcircuits Using Paired Patch-Clamp Recordings in Acute Brain Slices -- Outside-Out ‘Sniffer-patch’ Clamp Technique for in situ Measures of Neurotransmitter Release -- A Cost Effective Method for Preparing, Maintaining and Transfecting Neurons in Organotypic Slices -- Acute Brain Slice Methods for Adult and Aging Animals: Application of Targeted Patch Clamp Analysis and Optogenetics -- Synaptic Connectivity in Engineered Neuronal Networks -- Modeling of Action Potential Generation in NG108-15 Cells -- Whole-Cell Patch-Clamp Recordings in Freely Moving Animals -- Pressure-Polished Borosilicate Pipettes are “Universal Sealer” Yielding Low Access Resistance and Efficient Intracellular Perfusion -- Current Recordings at the Single Channel Level in Adult Mammalian Isolated Cardiomyocytes -- Dynamic Clamp as a Tool to Study the Functional Effects of Individual Membrane Currents -- Dynamic Clamp in Cardiac and Neuronal Systems Using RTXI -- Ion Selectivity of Pore-Forming Peptides and Ion Channels Measured in Xenopus Oocytes -- Principles of Single-Channel Kinetic Analysis.
Keywords: Neurosciences; Human physiology; Neurosciences; Human Physiology